Taṭwīr Kitāb al-Lughat al-‘Arabiyyat ‘ala Asās al-Dzakā’at al-Muta’addidat Bi al-Taṭbīq ‘ala al-Madrasat al-Ibtidāiyyat al-Islamiyyat al-‘Alamiyyat Mālanj - Muhimmatul Mukaromah (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2022)
This study aims to determine the development of Arabic language textbooks based on Multiple Intelligences at the Madrasah Ibtidaiyah/Islamic Elementary School level and the effectiveness of their use in the classroom. This research is based on the problem finding that some of the textbooks used in some schools are still less effective for learning Arabic. In some Arabic textbooks at the Madrasah Ibtidaiyah/Islamic Elementary School level, there are many long texts for learning istima', kalam, and qiro'ah so that they are not suitable for basic level learners. Some books focus only on the cognitive domain, and do not accommodate various types of intelligence so that they are less helpful for students to develop. This study uses Research and Development (R&D) research methods and data collection is carried out by observation, interviews, questionnaires, and tests. The test subjects consisted of content experts, instructional design experts, textbook design experts, and grade 3B students of SD Islamic Global School Malang as the target users of the product. The results of this study indicate: 1) Multiple Intelligences-based Arabic textbooks were developed based on needs analysis and field data, then designed in the form of an initial draft to be tested by three experts, then revised and tested individually, and field tested on grade 3B students. SD Islamic Global School Malang. The second and third stage revisions were carried out after the trial process. The revised result is the final product of this research, 2) The use of the the book